Assessing the nitrogen supply of hairy vetch in a soybean-wheat sequence - Rodriguez, Maria Pia; Carcedo, Ana Julia; Correndo, Adrían; Crespo, Cecilia; Carciochi, Walter Daniel; Ciampitti, Ignacio Antonio; Barbieri, Pablo (Elsevier, 2024)
Context: Legume cover crops are often considered a valuable alternative for supplying nitrogen (N) to cropping systems. However, certain pathways of N released from their residues to successor crops remain unclear. Objectives: Aiming to assess N contribution and residual N from hairy vetch (Vicia villosa Roth.) cover crop in succeeding crops, we examined i) soil N availability and mineralizable-N, ii) crop yields, and iii) plant N sourcing within the soybean [Glycine max (L.) Merrill]-wheat (Triticum aestivum L.) cropping sequence in the southeastern Argentine Pampas. Methods: Three field experiments were conducted over three seasons: E1 (2018/19), E2 (2019/20), and E3 (2020/2021) in the southeast of Buenos Aires province. The crop sequence studied was hairy vetch/soybean-wheat. Factors investigated were hairy vetch inclusion and bare fallow, and wheat N fertilizer (150 and 0 kg N ha−1). Hairy vetch aboveground dry matter and its N concentration were measured at hairy vetch termination and six times thereafter (residues) during the succeeding soybean, using the litter bag method. Soybean biomass, N concentration, and the relative abundance of ureides (RAU) as an indicator of N fraction derived from biological nitrogen fixation (BNF), were examined. Soil NO3--N and anaerobically incubated N (Nan) were sampled during the soybean season and at wheat sowing. At physiological maturity, soybean and wheat grain yields, along with grain N concentrations, were determined. Results: Hairy vetch N released during soybean season ranged from 79 to 175 kg N ha−1. Soil NO3--N content at soybean sowing increased 5.5 kg ha−1 per Mg of hairy vetch dry matter, while Nan increased 3.6 mg kg−1 per Mg of hairy vetch dry matter. Soybean seed yields, seed N content, and N uptake showed no significant change with increased hairy vetch dry matter. Likewise, RAU at R5 decreased from 2.4 to 5.5 units (%) per Mg of hairy vetch dry matter. Concerning wheat, hairy vetch produced a slight increase in soil residual N at sowing. Only in one experiment (E1), hairy vetch dry matter led to improvements in wheat grain yield and N content. Conclusions: Our study outlined new insights into hairy vetch N contribution, primarily linked to increased soil N availability in the immediate soybean, the relatively higher soybean N uptake from soil compared to BNF, and the dilution of soil N contribution to wheat as second crop in the sequence. Implications: These findings support the recommendation of using hairy vetch as a predecessor for an immediate cereal or non-N fixing crops.